Factors predicting technical failure of endoscopic transpapillary gallbladder drainage for acute cholecystitis - Noriyuki Hirakawa; Kenjiro Yamamoto; Atsushi Sofuni; Takayoshi Tsuchiya; Kentaro Ishii; Reina Tanaka; Ryosuke Tonozuka; Shuntaro Mukai; Kazumasa Nagai; Yukitoshi Matsunami; Hiroyuki Kojima; Hirohito Minami; et al. (DEN Open)
Abstract Objectives Endoscopic transpapillary gallbladder drainage (ETGBD) is a highly technical procedure, but few studies have evaluated factors that predict its technical success. Therefore, in this study, we sought to identify predictors of technically successful ETGBD. Methods One hundred and eighty‐two patients who underwent ETGBD for acute cholecystitis at our hospital were retrospectively investigated. Factors associated with technical failure were identified by focusing on clinical characteristics, anatomical features (direction of the cystic duct branch and course of the cystic duct), and procedural factors (cystic duct and gallbladder with or without contrast and cystic duct injury). Results The technical success rate was 84.6% (154/182) and the clinical success rate was 96.1% (148/154). The adverse event rate was 11.0% (20/182; cystic duct injury in 13 patients, pancreatitis in six, and liver abscess in one. Univariate and multivariate analyses identified the right cranial direction and spiral‐type course of the cystic duct to be significant anatomical features and cystic duct injury to be a significant procedural feature contributing to the technical failure of ETGBD. Conclusions ETGBD is a highly practical procedure for patients with acute cholecystitis. However, difficulty is encountered in some cases because of anatomical and procedural factors. Our results suggest that ETGBD may be difficult and thus should not be performed in cases with the right cranial direction or spiral‐type course of the cystic duct or those with cystic duct injury.